Exploring the effect of learning styles on learning achievement in a u-Museum. Issue 5 (4th July 2018) - Chen, Chia-Chen; Chen, Chien-Yi
ABSTRACT: In recent years, mobile technology has been developing rapidly and has been widely used. There are many successful cases of mobile technology applied greatly in today's teaching and even combined with sensing devices to overcome the limitations of traditional learning environment. In order to make teaching more diversified, teachers currently treat field trips as one of the major ways to aid traditional classroom teaching. Based on Keller's ARCS motivation model, this study used the natural disaster section in the sixth graders' Natural Science-Taiwan subject as an example and application of radio frequency identification (RFID) technology in mobile devices to develop a context-aware ubiquitous learning system to be applied in the 921 Earthquake Museum of Taiwan. With the guide of the system, learners can use mobile carriers to receive content information displayed in the Museum for learning. This study conducted experiment in the 921 Earthquake Museum of Taiwan to explore whether using the system for learning significantly improves learning outcomes and motivation in comparison to traditional navigation learning. Felder & Silverman's theory of learning style was incorporated to explore whether there exists differences in learning performance and outcome among learners with different learning styles so design and strategies for future teaching system can be improved.